Do Private Utilities Outperform Local Government-Owned Utilities? Evidence from German Retail Electricity - Caroline Stiel; Astrid Cullmann; Maria Nieswand (German Economic Review, 2018)
Against the background of remunicipalisation trends in European public service sectors, this paper estimates firm-level productivity for German electricity retailers and tests whether the ownership type has a significant impact on productivity. We specify a production function for the retail sector with labour and external services as main inputs, which is estimated using a control function approach. Employing a newly constructed dataset on German utilities by the German Federal Statistical Office for the years 2003-12, we find that firm-level productivity generally increased until 2008 but not afterwards. We do not find any evidence for ownership having an impact on productivity.
Keywords: 330; productivity; retail electricity; ownership; structural prodction function